Hash-Tree Anti-Tampering Schemes - Moss, Ben; Ashman, Helen (2002)
Procedures that provide detection, location and correction of tampering in documents are known as anti-tampering schemes. In this paper we describe how to construct an anti-tampering scheme using a pre-computed tree of hashes. The main problems of constructing such a scheme are its computational feasibility and its candidate reduction process. We show how to solve both problems by the use of secondary hashing over a tree structure. Finally, we give brief comments on our ongoing work in this area.